Who’s the BOSs : Shedding New Light on Businesses of the State - World Bank (Washington, DC, 2022)
Supporters of state presence in economic activities cite the potential for catalyzing growth in new sectors or ensuring the wider availability of goods or services for the public, particularly in response to crisis. However, firms owned by the state are a potential source of market distortions and crowding out of the private sector through subsidies and preferential access to finance and land. The risks are even higher when state-owned enterprises (SOEs), a subset of businesses of the state, have the dual role of market player and regulator by controlling prices and licenses and raising barriers to potential competitors. Before addressing the contributions and difficulties generated by firms with state participation regarding the functioning of markets, counting the full extent of the state’s presence in the economy is critical. The World Bank’s new global Businesses of the the State database marks a big leap forward in gathering the necessary information for analysis. Comprehensive mapping of state ownership captures the extent of a state’s footprint and its links across firms and markets. The BOS database is the first systematic attempt to capture the decision of the state to participate in firms across the corporate sector. Seven new facts extracted from the World Bank’s new Businesses of the State (BOS) Global Database Project show the state’s footprint in commercial activities is bigger than previously captured, and in unexpected places.